Student Attendance System using Facial Recognition - Zainal Ariffin, Muhammad Ikhwan; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2023)
Student Attendance System using Facial Recognition is a web application that helps both lecturer and student to record attendance while minimizing time consumption during the recording process. Traditionally, recording attendance consumes a significant amount of time because it involves each student to sign their attendance on a piece of paper. Thus, the utilization of facial recognition technology can help in reducing the time used to record attendance during teaching and learning process. Additionally, the system proposed can reduce error such as when a student was not given the attendance sheet by mistake. The methodology applied for the system is Spiral Model. Software such as Visual Studio Code, PostgreSQL, Django are used to develop the system. The system is expected to minimize the time used and error when recording attendance.